Combination of conventional elastocaloric and magnetocaloric effects in a Co37Ni35Al28 ferromagnetic shape memory alloy. (15th March 2018) - Khan, Muhammad Tahir; Wang, Yu; Wang, Cong; Liao, Xiaoqi; Yang, Sen; Song, Xiaoping; Ren, Xiaobing
Abstract: The elastocaloric and magnetocaloric effects in a polycrystalline ferromagnetic shape memory alloy Co37 Ni35 Al28 are investigated. The alloy shows conventional elastocaloric effect with entropy change of − 5.05 J kg − 1 K − 1 under 350 MPa. The temperature change of its elastocaloric effect is over 1 K within a working temperature range of 80 K covering ambient temperature. Moreover, the alloy also shows conventional magnetocaloric effect. The conventional elastocaloric and magnetocaloric effects of the alloy possess the same sign of entropy change and temperature change, the simultaneous use of multiple caloric effects can be achieved by applying stress and magnetic field, which improves its overall refrigeration capability. Graphical abstract: Image 1